Implementasi Metode Profile Matching Dengan Weighted Product Pada Seleksi Staf Operator Komputer (Studi Kasus : UPTD Pendidikan Kecamatan Tambakboyo Kabupaten Tuban Jawa Timur) - Oktavianis Kartikasari; Nurul Hidayat; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Getting qualified human resources to fill vacant positions is certainly not an easy matter. Both agencies and companies generally use selection to get staff according to established criteria. Selection is done because it sees the important role of staff in helping run the wheel of the workplace concerned. Getting the staff with the desired abilities will certainly have a good impact not only on the related places but also on the existing resources. This research uses Profile Matching and Weighted Product method to assist the selection process. Both methods are selected because the Profile Matching is considered to help the human resources or team selection in giving the weight of the value according to the level of importance of the criteria for the position offered. While Weighted Product is the best method according to Vijay Manikrao Athawale and Shankar Chakraborty for robot selection. Based on the test performed, the accuracy obtained from the incorporation of this method is 80%.